Ultrafast Laser Processing of Diamond Materials: A Review - Apostolova, Tzveta; Kurylo, Vasyl; Gnilitskyi, Iaroslav (Frontiers in Physics, 2021)
Diamond laser engineering is of great importance for designing devices which find applications in radiation sensing and quantum technologies. A review of the present state of the art of experimental and theoretical studies on ultrashort laser irradiation of diamond is presented. Using a wide range of laser parameters the optimization of a specific laser-induced processes such as change of material optical properties, high precision nano-structuring or phase transition, requires quantitative understanding of the microscopic processes underlying ultrashort strong field excitation in diamond as a wide band gap material. Relevant theoretical approaches describing femtosecond laser irradiation of diamond and their connection to experiment are presented.